The new engagement game: the role of gamification in scholarly publishing. Issue 4 (1st October 2013) - ARMSTRONG, David
ABSTRACT: Gamification – the application of game mechanics to solve problems and engage users – is gathering significant momentum in the wider business world, and there are many ways in which it could benefit librarians, academic publishers, and learned societies. At its core, gamification is a way of tapping into motivational forces to increase individual investment in a system, process, or resource; applied correctly, these mechanics could be used to increase engagement with a publisher's back catalogue, drive society members to explore the value their membership offers, and encourage students to connect with on‐campus learning resources. Gamification can help satisfy both business and audience objectives, but frameworks have to be carefully designed to avoid some of the common pitfalls that such systems face. Although there are few examples of gamification at work in the learned publishing sector, those who are willing to explore, experiment, and iterate on solutions will be better placed to meet the needs of the increasing 'digital native' student and academic population.